Cranio-Caudal Identification and Preservation of Spinal Accessory Nerve during Modified Radical Neck Dissection - Pushkar P. Waknis; Ravina Dharamsi; Mrinal Gawali; Divya Palanisami (Indian Journal of Dental Research)
Introduction: The spinal accessory nerve (SAN) is encountered during neck dissection surgeries and is at the highest risk for iatrogenic injury, which may lead to shoulder syndrome. This functional deformity can be avoided by preservation of SAN in modified radical neck dissection (MRND). Description: Many techniques are described in the literature for SAN preservation, one of which is the identification of Erb’s point and dissection in the posterior triangle where the SAN leaves the sternocleidomastoid (SCM) muscle. However, this technique for identification and preservation of SAN requires a skilled and trained surgeon to avoid any iatrogenic injury to SAN. Conclusion: Therefore, a study was carried out on 30 patients to find if the cranio-caudal dissection of SAN helps in the preservation of the nerve during MRND surgeries at the beginner’s level.